Recent trends in spinal infections: retrospective analysis of patients treated during the past 50 years - Nagashima, Hideki (Springer-Verlag, 2009)
We retrospectively reviewed the medical charts of 210 consecutive patients treated for spinal infection in Tottori University Hospital in Japan between 1956 and 2005. Until 1995, spinal infection was under control in this series; however, during the last decade, it has been on the rise. Male predominance had been gradually progressing, and 69% of the patients were male during the last decade. Patients with spinal infection were aging, and the ratio of immunocompromised hosts dramatically increased to 53%. Until 1995, the percentage of patients with tuberculous spondylitis had been declining; however, the incidence has been on the rise during the last ten years. The organism was detected in 64% of patients treated between 1996 and 2005, of which Staphylococcus aureus was detected in 49%. Moreover, methicillin-resistant S. aureus was detected in 61% of patients with S. aureus. There were no immigrants or cases with human immunodeficiency virus in this series.